(untitled) (Anclajes, 2016)
Between the two poles of signification in Sergio Chejfec’s novel El aire (1992), that is, the city and the country as symbolic compendia of various strongly rooted cultural tensions, there is a space of indeterminacy that suspends the dichotomies derived from that canonical territorial division and establishes a certain way of thinking of and about literature. This article looks forward to emphasizing some of the ways in which that territory of unresolved tensions appears and how it interrogates all the codified categories the fall under in the city/country dichotomy in the light of the sentimental air that runs though the entire novel.